2003
DOI: 10.1038/sj.bmt.1704198
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of busulfan vs total body irradiation containing conditioning regimens for children with acute lymphoblastic leukemia: A Pediatric Blood and Marrow Transplant Consortium study

Abstract: Summary:Conditioning regimens for children with ALL have generally included total body irradation (TBI), which may result in significant sequelae. The primary aim of this study was to evaluate the outcome for children with ALL undergoing allogeneic stem cell transplant (SCT) with either busulfan (Bu) or TBI regimens. Patients o21 years with ALL undergoing allogeneic SCT were eligible. Conditioning included either Bu or TBI, with etoposide 40 mg/kg and cyclophosphamide 120 mg/kg. Randomization was stratified ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
5
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 29 publications
4
121
5
3
Order By: Relevance
“…3 This study included children, for whom randomized trials also demonstrated an advantage for TBI-based regimens. 13,14 In the Spanish study, multivariable analysis also identified age greater than 16 years as an adverse predictor of outcome. Our analysis found no significant impact of age or conditioning regimen on either EFS or OS in an adult population.…”
Section: Discussionmentioning
confidence: 99%
“…3 This study included children, for whom randomized trials also demonstrated an advantage for TBI-based regimens. 13,14 In the Spanish study, multivariable analysis also identified age greater than 16 years as an adverse predictor of outcome. Our analysis found no significant impact of age or conditioning regimen on either EFS or OS in an adult population.…”
Section: Discussionmentioning
confidence: 99%
“…16 In ALL patients, TBI is widely used as it has not been shown that TBI could be replaced by chemotherapy. [17][18][19] Since the late 1970s, both TBI therapy and supportive care have greatly improved, and this may result in less frequent late effects among the more recently treated survivors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings seem to confirm the significant anti-leukemic efficacy of TREO-prep-reg, which appears to be comparable with that of standard-prep-reg in childhood hematological malignancies. 43,46,49,50 The significant anti-leukemic effect of TREO-based conditioning regimens along with their low toxicity, makes them also an attractive alternative to RIC regimens, especially for patients with high-risk hematological malignancies, in whom relapse remains the most common obstacle to a successful outcome of RIC. 4,[35][36][37] However, as a prodrug nonenzymatically activated to alkylating mono-and diepoxides, TREO demonstrates gonadotoxicity and mutagenicity, and thus monitoring and evaluation of its long-term effects, including secondary MDS in children demonstrating mixed chimerism, will be of special importance in children conditioned for HSCT with high-dose TREO.…”
Section: Discussionmentioning
confidence: 99%